2011
DOI: 10.1590/s0102-695x2011005000023
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, cytotoxic and antibacterial activities of Cleome viscosa leaves

Abstract: Abstract:The methanol extract of the dried leaves of Cleome viscosa L., Cleomaceae, was investigated for its possible antinociceptive, cytotoxic and antibacterial activities in animal models. The extract produced significant writhing inhibition in acetic acid-induced writhing in mice at the oral doses of 250 and 500 mg/kg body weight (p<0.001) comparable to the standard drug diclofenac sodium at the dose of 25 mg/kg of body weight (p<0.001). The crude extract produced the most prominent cytotoxic activity agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
(23 reference statements)
2
9
0
3
Order By: Relevance
“…A Cleome viscosa é uma integrante da família Cleomaceae que demonstrou ser capaz de inibir diversas cepas bacterianas in vitro através da metodologia da difusão em disco, dentre as cepas testadas estão Shigella sonnie, Staphylococcus aureus e Vibrio cholera. O efeito antibacteriano foi considerado relevante e os halos de inibição variaram de 10,76 a 16,34mm para Cleome viscosa e 28,90 a 44,88 no controle (BOSE et al, 2011). Sua utilização tem sido direcionada a diversos problemas de saúde como é o caso da inflamação, problemas hepáticos, diarreia e febre.…”
Section: Estudo Sobre O Potencial Antimicrobiano Dos óLeos Essenciais De Partes Superiores Daunclassified
“…A Cleome viscosa é uma integrante da família Cleomaceae que demonstrou ser capaz de inibir diversas cepas bacterianas in vitro através da metodologia da difusão em disco, dentre as cepas testadas estão Shigella sonnie, Staphylococcus aureus e Vibrio cholera. O efeito antibacteriano foi considerado relevante e os halos de inibição variaram de 10,76 a 16,34mm para Cleome viscosa e 28,90 a 44,88 no controle (BOSE et al, 2011). Sua utilização tem sido direcionada a diversos problemas de saúde como é o caso da inflamação, problemas hepáticos, diarreia e febre.…”
Section: Estudo Sobre O Potencial Antimicrobiano Dos óLeos Essenciais De Partes Superiores Daunclassified
“…12 Phytochemical screening studies of Cleome genus have been found phenolic compounds, alkaloids, terpenoids, flavonoids, Fatty acids, coumarino-lignan, rich source of nutrients, especially vitamins A and C, protein, gallotannins, saponins, iridoid, hexacosanol and kaempferol. 7,[13][14][15][16][17] Therefore, finding natural antibacterial, antifungual and antioxdant agents with similar therapeutic effect could be a promising approach, which is safer and healthier. 18 To date, the chemical composition and…”
Section: Introduction U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…This plant possesses Ayurveda medicine such as seed used for anthelmintic, leaves used in wound healing, and fever [9,10]. Moreover, pharmacological of this plant is evaluated as an anesthetic, anti-diarrhea, anti-inflammatory, antimalarial, and antipyretic activities [11][12][13]. Moreover, the phytotoxic activity of C. viscosa showed inhibitory effect on germination and growth in agricultural product [14].…”
Section: Introductionmentioning
confidence: 99%